Hydrogen Homes Dataset for H2 Acceptance Matrix analysis - Gordon, Joel; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Cranfield University, 2024)
This dataset records qualitative answers (written statements) given by respondents at the end of an online survey (programmed in Qualtrics) on domestic hydrogen in the United Kingdom (N= 1845). The open-ended question was specified as follows: lease use this text box to explain more about your attitudes towards hydrogen or any other reflections on this topic. Around two-thirds (N = 1213) provided written responses, which were subsequently coded according to one-dimensional (hydrogen pessimist, hydrogen sceptic, hydrogen cautious, hydrogen neutral, hydrogen curious, hydrogen hopeful, or hydrogen optimist) and multi-dimensional responses (e.g. hydrogen hopeful yet cautious, or hydrogen cautious but otherwise neutral etc.) 81.8% of respondents expressed a one-dimensional perspective (N = 992). The data collection period ran between 06/10/2023–23/12/2023. The survey duration was approximately 15–20 minutes. In published materials, we use the term Hydrogen Homes (H2H) dataset to denote outputs from this project.
Keywords: 'Hydrogen acceptance'; 'Consumer attitudes'; 'Public perceptions'; 'Emotional responses'; 'Sustainable energy futures'; 'Low-carbon heating and cooking'; 'Net Zero Energy'